2019
DOI: 10.1111/jcmm.14379
|View full text |Cite
|
Sign up to set email alerts
|

Paeoniflorin protects spiral ganglion neurons from cisplatin‐induced ototoxicity: Possible relation to PINK1/BAD pathway

Abstract: The objective of this study was to elucidate whether paeoniflorin (PF) exerted an effect on cisplatin‐induced spiral ganglion neuron (SGN) damage, with special attention given to the role of PINK1/BAD pathway in this process. Middle cochlear turn culture and C57BL/6 mice were utilized to identify the character of PF in vitro and in vivo. We found that cisplatin treatment led to SGN damage, in which reactive oxygen species (ROS) generation increased, PINK1 expression decreased, BAD accumulation on mitochondria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 37 publications
(93 reference statements)
0
11
0
Order By: Relevance
“…4F). Previous reports have documented cisplatin-induced damage to the stria and spiral ganglion neurons, reinforcing these cells as sensitive to cisplatin treatment (63)(64)(65)(66).…”
Section: Dabrafenib Inhibits Phosphorylation Of Erk Kinase In the Scsmentioning
confidence: 62%
“…4F). Previous reports have documented cisplatin-induced damage to the stria and spiral ganglion neurons, reinforcing these cells as sensitive to cisplatin treatment (63)(64)(65)(66).…”
Section: Dabrafenib Inhibits Phosphorylation Of Erk Kinase In the Scsmentioning
confidence: 62%
“…Paeoniflorin is a bioactive compound isolated from the Chinese herbal medicine plant Paeonia lactiflora , which has a wide range of anti‐inflammatory, analgesic and immunomodulatory effects 50 . In addition, paeoniflorin is a potential neuroprotective agent, which has been proved to reduce neuronal damage by reducing the secretion of IL‐6 and other inflammatory factors or reducing the level of autophagy 51–53 . Recent studies have confirmed that paeoniflorin significantly improves BIPN, which may regulate PARKIN‐mediated mitochondrial autophagy and mitochondrial damage by reducing IL‐6 levels 44 .…”
Section: Prevention and Treatmentmentioning
confidence: 99%
“…A calpain inhibitor PD150606 could suppress calpain by mediating AIF induced by glutamine and caspase-12 activation, restraining apoptosis processing and SGNs in vitro [87]. Meanwhile, allicin [104] and curcumin [105] were found to protect SGNs from ototoxic drugs, when paeoniflorin and neurotrophin might exert as protective effect through the PINK1/BAD pathway [89,106].…”
Section: Apoptosis Inhibitorsmentioning
confidence: 99%